NACA impact on APP aggregation : the ability of NACA to interfere with aggregation of Amyloid precursor protein (APP) molecules - Fanney Gunnarsdóttir 1993- (2024)
This research builds on the results of previous phase IIa clinical trials conducted by Arctic Therapeutics. The outcome from that trial was favorable and suggests that N-Acetyl Cysteine (NAC) is a good option for treating Hereditary Cystatin C Amyloid Angiopathy (HCCAA). This research is based on cell culture, plasmid insertion, and Western blot analysis of cells treated with N-acetyl-cysteine-amide (NACA), focusing on the E693Q mutation that causes Hereditary Cerebral Hemorrhage with Amyloidosis – Dutch type (HCHWA-D). The thesis examines the broader context of cerebral amyloid angiopathy (CAA) and also aims to answer the research question of whether NACA can be used to break down the disease-causing amyloids caused by the E693Q mutation in the APP protein in HEK293T cell models. The methodology is divided into three main phases: HEK293T cell maintenance, plasmid transfection, and protein analysis through Western blot, seeking to optimize the protocols for accuracy and efficiency. The theoretical framework focuses on the pathophysiology of amyloidosis, the molecular biology of APP, and the oxidative stress mechanisms associated with CAA, a condition characterized by the accumulation of amyloid proteins in cerebral blood vessels, leading to increased risk of haemorrhage and neurological decline. The study aims to contribute to the understanding of NACA's potential as a therapeutic agent against CAA by inhibiting the aggregation of amyloid proteins and provide insights into possible treatment options for related neurodegenerative diseases. Despite the results not clearly showing whether NACA was breaking down myelin protein, it was noticed that changes in the ratios of Viafect solution, where ratios 6:1 and 7:1 performed better furthermore results were better when antibodies from Sigma were used: Monoclonal ANTI-FLAG M2 primary antibody (mouse) and anti-mouse IgG Peroxidase secondary antibody (rabbit). Keywords: N-acetyl-cysteine amide (NACA), Amyloid Precursor Protein (APP), E693Q mutation, Cerebral Amyloid ...